Clinical study of liver blood flow in man measured by 133Xe clearance after portal vein injection. Issue 12 (December 1977) - Sherriff, S B; Smart, R C; Taylor, I
Abstract : During the course of a clinical trial to assess the value of adjuvant liver perfusion of 5-fluorouracil after surgery for colorectal cancer, liver blood flow was measured in 14 patients. Access to the portal circulation was achieved by dilatation and cannulation of the obliterated umbilical vein. The clearance from the liver of a bolus of 133Xe was monitored using a gamma-ray camera so that blood flow from different areas of the liver could be calculated. The clearance curve of 133Xe was a double exponential of which the initial fast component accounted for a consistently high proportion of the total clearance. The perfusion studies have shown wide differences in blood flow to the various areas of the liver in the same patient, in addition to a wide variation in perfusion rate between the 14 patients. This technique of quantitative estimations of liver blood flow to different areas of the liver may have importance in planning operative procedures and understanding the haemodynamic mechanisms involved in liver disease.